2020
DOI: 10.1111/1467-9817.12339
|View full text |Cite
|
Sign up to set email alerts
|

Does questioning strategy facilitate second language (L2) reading comprehension? The effects of comprehension measures and insights from reader perception

Abstract: Background Extensive second language (L2) reading research has examined the effects of comprehension strategies on comprehension performance. Often ignored, however, is the potential impact of comprehension measures that differ in cognitive complexity, which might cause potential bias when interpreting the (in)effectiveness of comprehension strategies. Method With a total of 54 Chinese learners of English at college in China, this study examined whether the effect of the questioning strategy (answering what an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…Meanwhile, relatively proficient readers in Low Profile may either have been selective in applying strategies due to high metacognitive awareness, have needed few strategies due to their large vocabulary, or have used such strategies automatically without realising it. Additionally, the comprehension task type (multiple choices in our study) might also influence the associations between strategy use and reading performance (Li et al, 2022). Therefore, it is illogical to expect linear, additive associations between strategy use and language performance (Yamamori et al, 2003).…”
Section: Associations Between Individual Factors and Self-regulated L...mentioning
confidence: 78%
“…Meanwhile, relatively proficient readers in Low Profile may either have been selective in applying strategies due to high metacognitive awareness, have needed few strategies due to their large vocabulary, or have used such strategies automatically without realising it. Additionally, the comprehension task type (multiple choices in our study) might also influence the associations between strategy use and reading performance (Li et al, 2022). Therefore, it is illogical to expect linear, additive associations between strategy use and language performance (Yamamori et al, 2003).…”
Section: Associations Between Individual Factors and Self-regulated L...mentioning
confidence: 78%
“…Many previous studies confirm that RTS is an effective reading strategy that significantly supports reading comprehension (Ahmadi, 2016;Cockerill et al, 2022;Dew et al, 2021;Hamdani, 2020;O'Hare et al, 2019;Pilten, 2016;Rojabi, 2021;Thurston et al, 2020). In addition, as in RTS, students read better in learning processes used by inquiry strategies (Ahmadi et al, 2021;Ariawan, & Winoto, 2021;Brown, & Pyle, 2021;Bui et al, 2021;Castells et al, 2021;Liu, 2021;Parjan, & Mohamad, 2021;Stuckelman et al, 2022).…”
Section: Innoeduca International Journal Of Technology and Educationa...mentioning
confidence: 83%
“…These varying types of questions may, for instance, ask students to locate key information in the text, combine key information across paragraphs, or integrate key information with their background knowledge. Most research studies confirm that more difficult question items are more likely to elicit higher level cognitive reading strategies (e.g., Alderson, 2000;Anderson et al, 1991;Davey, 1988;Liao, 2021;Liu, 2021;Rupp et al, 2006), especially those tapping implied information, such as inferential questions (Davey, 1988). Answering different types of questions requires a diversity of reading skills, which may affect the proportion of item distribution for each type of question.…”
Section: The Relationship Between the Number Of Items And The Number ...mentioning
confidence: 99%
“…Finally, question types may vary in terms of their difficulty because they require different kinds of strategies for comprehension processing. Research has revealed that question types significantly influence the use of reading strategies; specifically, more difficult items tend to require higher level cognitive reading skills (e.g., Anderson et al, 1991; Davey, 1988; Liao, 2021; Liu, 2021; Rupp et al, 2006). Davey (1988), for instance, found that question items that require inferential processing (e.g., inferential and vocabulary questions) are more difficult than those that require the examinees to locate explicitly stated information in the text (e.g., factual questions), thereby motivating them to use higher order reading strategies.…”
Section: Literature Reviewmentioning
confidence: 99%